Association of Red Blood Cell and Platelet Parameters with Metabolic Syndrome: A Systematic Review and Meta-Analysis of 170,000 Patients - Mahmood, Aysal; Samad, Saba; Haider, Hoorain; Hassan, Wardah; Mushtaq, Rabeea; Perwaiz, Aimen; Ali, Abraish; Azharuddin, Muhammad (Hormone and Metabolic Research, 2024)
This systematic review and meta-analysis aim to establish associations between metabolic syndrome (MetS) and erythrocyte and platelet markers, contributing to improved diagnostic tests for identifying individuals at risk. Observational studies and Randomized Controlled Trials (RCTs) were included. The standardized mean difference (SMD) and 95% confidence intervals (CI) of erythrocyte and platelet markers between individuals with and without MetS were used as effect size (inverse variance model). Methodological quality assessment was conducted using the Newcastle-Ottawa scale (NOS) for observational studies and the Cochrane Risk of Bias tool 2.0 for RCTs. The analysis included 51 articles. Compared to controls, individuals with MetS exhibited significantly higher concentrations of mean red blood cell count [Standardized Mean Difference (95% CI): 0.15 (0.13−0.18); p<0.00001], hemoglobin [0.24 (0.18−0.31); p<0.00001], blood platelet count [5.49 (2.78–8.20); p<0.0001], and red blood cell distribution width [(0.55 (0.05–1.04); p=0.03]. Regarding mean platelet volume [0.16 (– 0.03 to 0.35); p=0.10] and platelet-to-lymphocyte ratio (PLR) [7.48 (–2.85–17.81); p=0.16], a non-significant difference was observed in patients with MetS. There was no statistically significant difference in hematocrit counts between the two groups [0.47 (–0.40 to –1.34); p=0.29]. Biomarkers such as mean red blood cell count, hemoglobin, blood platelet count, and RDW are associated with higher levels in patients in MetS, whereas mean platelet volume and PLR tend to be lower. These markers can potentially provide new avenues for early diagnosis of MetS.
Keywords: red blood cell; platelet; red blood cell distribution width; erythrocyte